The discovery of the lymphatic system in the seventeenth century. Part IV: the controversy. Issue 4 (4th July 2017) - Suy, Raphael; Thomis, Sarah; Fourneau, Inge
Abstract: A controversy over the transport of chyle and lymph started a few weeks after the publication of Pecquet's Experimenta Nova Anatomica. There are records of nearly seventy people who had an active interest in this matter. Three issues were discussed: the purpose of the liver and especially its haematopoietic function, the capacity of the thoracic duct to transport all chyle, and the purpose of the lymph vessels. The controversy over the use of the lacteals and the lymph vessels subsided about 20 years after the first publication of the new theories. In this contribution, we focused on the ideas of William Harvey, since his ideas were close to the real configuration of the lymphatic system, and on the peculiar anatomical set-up of Louis De Bils (ca 1624-1669), an obscure French-Flemish non-professional anatomist, who was the initiator of a heated controversy in the Netherlands with his original ideas.